Transition of dome formation to sudden explosive eruptions at Popocatépetl, Mexico: magnetic indicators - Martin-Del-Pozzo, Ana Lillian; Santos Morales, César Alberto (Frontiers in Earth Science, 2024)
Transitions from effusive to explosive activity can increase hazards making it crucial to understand the transition precursors. After more than 80 cycles of crater-dome extrusion and destruction from 1996 on, Popocatépetl volcano experienced changes in its behavior from March 15 to July 18, 2019, when no lava domes were observed. Activity decreased considerably over this interval except for the unexpected explosions in March and June, that produced ash plumes reaching up to 14,000 m a.s.l. In order to investigate the causes of the transitions in eruptive style, we analyzed the magnetic time series from the magnetic monitoring network at Popocatépetl volcano between October 2018 and December 2019. The raw signals were analyzed by weighted differences (WD) based on the elimination of non-local changes from the total intensity values of the geomagnetic field and the discrete-time continuous wavelet transform was used to evaluate the local variations of energy within the time series. The high energy periods (linked to negative magnetic anomalies) are induced by magma ascent associated with movement within the conduit. They indicate that the sudden explosions were due to the ascent of several magma batches that were not able to reach the surface. Changes in the rheology of the lava are linked to the influx of several batches of magma with different compositions as well as to compaction by gas loss when ascending andesitic magma pushed out overlying more viscous degassed magma clearing the conduit, which can explain why these sudden explosions were more energetic. Several geophysical data sets as well as tephra composition were integrated to support this conclusion. The correlated multiparameters also confirm that geomagnetic volcano monitoring has been essential in understanding the processes that drive the observed changes in eruptive behavior.